Resolving the Unresolved: Using NESSI to Search for Unresolved Companions in Low-mass Disk Wide Binaries - Zachary D. Hartman; Gerard van Belle; Sébastien Lépine; Mark E. Everett; Ilija Medan (The Astronomical Journal, 2025)
Stellar systems consisting of three or more stars are not an uncommon occurrence in the Galaxy. Nearly 50% of solar-type wide binaries with separations >1000 au are actually higher-order multiples with one component being a close binary. Additionally, the higher-order multiplicity fraction appears to be correlated with the physical separation of the widest component. These facts have motivated some of our current theories behind how the widest stellar systems formed, which can have separations on the order of or larger than protostellar cores. However, it is unclear if the correlation between wide binary separation and higher-order multiplicity extends to low-mass binaries. We present initial results of an ongoing speckle imaging survey of nearby low-mass wide binaries. We find an overall higher-order multiplicity fraction for our sample of 42.0% ± 10.9%. If we include systems where Gaia indicates that a companion is likely present, this fraction increases to 62.0% ± 14.2%. This is consistent with previous results from both higher-mass stars and a previous result for low-mass wide binaries. However, we do not detect the expected increase in higher-order multiplicity fraction with separation, as was seen with previous studies. We briefly explore why higher-order multiplicity statistics could be different in low-mass stars, and what the significance might be for models of wide binary formation.